Glycosmis pentaphylla (Retz.) DC arrests cell cycle and induces apoptosis via caspase-3/7 activation in breast cancer cells. (20th June 2015) - Shoja, M.H.; Reddy, Neetinkumar D.; Nayak, Pawan G.; Srinivasan, K.K.; Rao, C. Mallikarjuna
Abstract: Ethnopharmacological relevance: Glycosmis pentaphylla (Retz.) DC belonging to the family Rutaceae has been traditionally used for the treatment of rheumatism, anaemia, jaundice, skin diseases, bronchitis etc. The plant is traditionally considered as anti-cancer medicine and used by the healers of Bangladesh to treat all types of cancers. Perhaps the key to many of its medicinal applications is its inherent anti-inflammatory property. Aim of the study: The present study is aimed at evaluating the effect of various fractions of G. pentaphylla (Retz.) DC leaves on the cell cycle and apoptosis of breast cancer cells viz. MCF-7 and MDA-MB-231. Materials and methods: Various extracts and fractions of the leaves of G. pentaphylla (Retz.) DC were studied for their cytotoxicity with the help of Sulforhodamine B assay, in MCF-7, MDA-MB-231 and Vero cell lines. The most active fractions were studied for their effect on the cell cycle of MCF-7 and MDA-MB-231 cells. Apoptotic studies were done using Hoechst staining, DNA fragmentation, Annexin V staining and caspase-3/7 activation assay in breast cancer cells. HPLC and HPTLC profiling of the active fractions were done. Results: HPTLC and HPLC profiling revealed the presence of lupeol, chrysin, quercetin, β-sitosterol and kaempferol as components in active fractions. Lupeol and chrysin are being reported in this plant for the first time. The studies showed that the selected fractions possess cell cycle inhibitory and apoptosis inducing effect on both MCF-7 and MDA-MB-231 cells. Apoptotic effect of the fractions on MCF-7 and MDA-MB-231 cells may be through the mitochondrial pathway by the activation of caspase-3/7. Graphical abstract: